ETHNOMATHEMATICS-BASED COGNITIVE ASSESSMENT MODEL FOR DYSCALCULIA STUDENTS: Jambi, Indonesia - Rahayu, Gebby Kusuma; Kamid; Yelli Ramalisa (Universitas Muhammadiyah Bengkulu, 2026)
This research is motivated by the learning difficulties experienced by students with dyscalculia in mathematics, particularly in understanding numerical concepts and performing basic arithmetic operations. This study aims to develop an ethnomathematics-based cognitive assessment model using the traditional congklak game and question cards to assess students' cognitive abilities in learning mathematics. This study uses the Research and Development (R&D) method with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research participants were six seventh-grade students with dyscalculia identified through a screening test. The developed model was tested with content validity and reliability tests. Content validity was validated by two experts, namely a subject matter expert and a media design expert, to evaluate the content and feasibility of the assessment model design. The results showed that the model achieved a validity score of 96.88% from the media expert and 93.75% from the subject matter expert, indicating that the product is valid. Furthermore, the reliability test using Inter-Rater Reliability (ICC) produced a value of 0.892, indicating very high reliability. These findings suggest that an ethnomathematics-based cognitive assessment model can be used as an alternative tool to assess the cognitive abilities of students with dyscalculia in adding and subtracting integers through culturally relevant learning activities. Keywords: Assessment cognitive; Ethnomathematics; Dyscalculia; Congklak